+0  
 
0
220
2
avatar+1318 

Solve the Equation

14-3(x+9)=5

ManuelBautista2019  Nov 6, 2017
 #1
avatar+92794 
+4

14 - 3(x+9) = 5     distribute the 3 across the terms in the parentheses

 

14 - 3x - 27   =  5       

 

14 - 27  - 3x  =  5

 

-13   - 3x  =   5  add 13 to both sides

 

-3x  =  18       divide both sides by -3

 

x  =   -6

 

 

cool cool cool

CPhill  Nov 6, 2017
 #2
avatar+537 
-1

14-3(x+9)=5

 

Subtract 14 from both sides.

 

14-3(x+9)-14=5-14

 

Simplify

 

-3(x+9)=-9

 

Divide both sides by -3

 

 

Simplify

 

x+9-9=3-9

 

Subtract 9 from both sides

 

x+9-9=3-9

 

Simplify

 

x=-6

 

laughlaughlaugh

ProMagma  Nov 6, 2017

12 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.